The Relationship Between Employee Satisfaction Levels, Financial Compensation and Employee Empowerment - Suseno Hadi Purnomo; Muhammad Faisal Arief; Elyas Albar (LPPM STIEM BONGAYA, 2026)
This research aims to find out and prove how much influence financial compensation and employee empowerment have on job satisfaction at the South Sulawesi Province BKKBN Agency. This type of research is quantitative. The population in this study were all employees of the South Sulawesi Province BKKBN Agency. Meanwhile, the sample was taken using population research with a total of 71 respondents. The sampling technique was carried out based on population research. The types of data used in this research are primary data and secondary data. The data analysis technique uses multiple regression analysis techniques using SPSS. The results of this research show that Financial Compensation and Employee Empowerment simultaneously do not have a significant effect on Job Satisfaction, Financial Compensation has a positive but not significant effect on Job Satisfaction, Employee Empowerment has a positive but not significant effect on Job Satisfaction. Job satisfaction.